The eye of the world [compact disc, unabridged] - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 1990)
When a village is attacked by trollocs, monsters thought to exist only in legends, three young men, Rand, Matt, and Perrin, flee in the company of the Lady Moiraine, a sinister visitor of unsuspected powers. Thus begins an epic adventure set in a world of wonders and horror.